THE EFFECT OF USING DIFFERENT TYPES OF OIL IN FEED ON THE CARCASS COMMERCIAL CUTTING CARCASS OF JOPER NATIVE CHICKEN - N.P.T., Arini,; Sukada, I K.; Nuriyasa, I M. (Jurnal Peternakan Tropika, 2023)
This study aims to find out the effect of the use of different types of oil in rations on commercial cutting carcass of native chicken. The research was conducted in Tabanan in July-August for 8 weeks. The study used a completely randomized design (CRD), with 5 treatments and 4 replications. Each experimental unit used 3 free-range chickens so that a total of 60 free-range chickens were used. The ration treatment (R) consisted of: R0: The ration without using oil, R1: The use of 3% palm oil in the ration, R2: The use of 3% used cooking oil in the ration, R3: The use of 3% fish oil in the ration, and R4: The use of 3% lard in ration. The observed variables include slaughter weight, carcass weight, carcass percentage, chest percentage, wing percentage, thigh percentage, and back percentage. The results showed that the use of 3% lard in feed (R4) produced the highest and most significant mean on the variables of slaughter weight and carcass weight. The use of different types of oil in feed did not affect the percentage of carcass, chest percentage, wing percentage, thigh percentage, and back percentage of native chickens. From the results of this study, it can be concluded that the use of 3% pork oil in native chicken rations resulted in slaughter weight and carcass weiht of native chickens. Key words: Native chicken, different types of oil, native chicken carcass, carcass commercial chips.